1994
DOI: 10.1111/j.1365-2923.1994.tb02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the competence of general practitioners in diagnosing generalized anxiety disorder using standardized patients

Abstract: The competence of general practitioners (GPs) in diagnosing anxiety neurosis was assessed using standardized patients (SPs) unknown to the doctors. Out of a computer-generated random sample of 100 general practitioners in Kuala Lumpur, 42 volunteered to participate in the study. The results showed that the GPs can be divided into three groups: group A made the correct diagnosis and informed the SPs about their condition (11.9%); group B prescribed tranquillizers and did not inform the SPs of the actual diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…For example, in a recent survey (7) detection rates for mental health problems were found to be considerably higher when screening was based on the General Health Questionnaire-28 (33.2 %) and the Schedules for Clinical Assessment in Psychiatry (SCAN) system (31.5%), than when screening involved direct GP observation (14.1%). Similar results were reported in a study (8) where trained medical students presented to GPs suffering from generalised anxiety disorder. Analysis indicated that 25 of 42 GPs studied made no diagnosis at all, or diagnosed only physical problems.…”
Section: Introductionsupporting
confidence: 89%
“…For example, in a recent survey (7) detection rates for mental health problems were found to be considerably higher when screening was based on the General Health Questionnaire-28 (33.2 %) and the Schedules for Clinical Assessment in Psychiatry (SCAN) system (31.5%), than when screening involved direct GP observation (14.1%). Similar results were reported in a study (8) where trained medical students presented to GPs suffering from generalised anxiety disorder. Analysis indicated that 25 of 42 GPs studied made no diagnosis at all, or diagnosed only physical problems.…”
Section: Introductionsupporting
confidence: 89%
“…A mixed methods study by Lewy [ 28 ] reported that paediatric residents ( n = 34) working with SPs attained an increased confidence in patient treatment, with 69% stating the intervention was “extremely helpful”. Shahabudin [ 30 ] trained medical students to act as patients presenting with various mental illnesses in order to assess the knowledge and diagnostic abilities of 42 general practitioners (GPs). The findings were grouped into three categories based on the performance of the doctors: group A—where 11.9% of the GPs informed the SPs of their anxiety diagnosis, group B—28.6% of the GPs prescribed medication for anxiety but did not inform the SP of their diagnosis and group C—where 59.5% of GPs did not diagnose nor treat the SP [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shahabudin [ 30 ] trained medical students to act as patients presenting with various mental illnesses in order to assess the knowledge and diagnostic abilities of 42 general practitioners (GPs). The findings were grouped into three categories based on the performance of the doctors: group A—where 11.9% of the GPs informed the SPs of their anxiety diagnosis, group B—28.6% of the GPs prescribed medication for anxiety but did not inform the SP of their diagnosis and group C—where 59.5% of GPs did not diagnose nor treat the SP [ 30 ]. This study highlighted the lack of consistent training, assessment and treatment in the GP management of mental health and highlights an opportunity for future research and investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Simulated patient methodology, including virtual and standardized patients, has been used effectively in clinical research to assess the impact of patient and provider variables on health care professionals’ decisions (Badger et al, 1994; Durante, McKinlay, Kasten, & Potter, 1997; M. D. Feldman, Franks, Epstein, Franz, & Kravitz, 2006; Kales, Neighbors, Blow, et al, 2005; Kales, Neighbors, Valenstein, et al, 2005; Kravitz et al, 2006; McKinlay, Lin, Freund, & Moskowitz, 2002; Schulman et al, 1999; Shahabudin, Almashoor, Edariah, & Khairuddin, 1994; H. N. Young, Bell, Epstein, Feldman, & Kravitz, 2006).…”
mentioning
confidence: 99%